Islamic Revivalism and Social Transformation in the Modern World - Ali, Jan A. (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
This reprint examines the panorama of contemporary Islamic revivalism in the modern world. Constituted by methodologically and ideologically a wide variety of revivalist movements, Islamic revivalism is a complex multidimensional global reality. In a local context, it is a socio-religious reaction to the failure of state-led modernization projects and to general socio-economic quandaries, and in international context, it is a reaction to the wide-ranging crises of modernity. The collection provides important insights into the reality of contemporary Islamic revivalism through an examination of myriad socio-cultural, economic, and political problems facing Muslims at micro- and macro-levels of everyday living. It explains how Islamic revivalist movements are engaged in revivalist activities commonly known as Islamization at an individual level as well as at a community level and reveals that as a global reality, contemporary Islamic revivalism is neither necessarily violent nor anti-modernity but an attempt by religiously motivated concerned Muslims to bring about a self-conceived positive social transformation of individual societies and the modern world at large.